A comparison between p16-positive head and neck cancer of unknown primary (HPV-HNCUP) and oropharyngeal squamous cell carcinoma (HPV-OPSCC): are they the same disease? - Balk, Matthias; Rupp, Robin; Sievert, Matti; Mantsopoulos, Konstantinos; Allner, Moritz; Grundtner, Philipp; Müller-Hübner, Sarina Katrin Ursel; Eckstein, Markus; Iro, Heinrich; Hecht, Markus; Gostian, Antoniu-Oreste (European Archives of Oto-Rhino-Laryngology, 2023)
Introduction: The following study aimed to answer the question if HPV-HNCUP and HPV-OPSCC are the same disease. Propensity score matching (PSM) was used to compare the oncological outcomes of both groups, in particular the 5-year overall survival rate (OS), the 5-year disease specific survival rate (DSS) and the 5-year progression free survival rate (PFS). Materials and methods: Firstly, between January 1st, 2007, and March 31st, 2020 a total of 131 patients were treated with HNCUP at our Department. Out of these, 21 patients with a confirmed positive p16 status were referred to surgery followed by adjuvant therapy. Secondly, between January 1st, 2000, and January 31st, 2017, a total of 1596 patients were treated with an OPSSC at our Department. Out of these, 126 patients with a confirmed positive p16 status were referred to surgery followed by adjuvant therapy. After PSM, 84 patients with HPV-OPSCC and 21 HPV-HNCUP remained in the study for further comparison. Results: The OS was 63.5% (95% CI 39.4–87.6) for HPV-HNCUP and 88.9% (95% CI 90.4–100.0) for HPV-OPSCC patients and therefore, significantly lower for the first mentioned (p = 0.013). The DSS was also significantly impaired for HPV-HNCUP (71.0%, 95% CI 46.3–95.7), in comparison with HPV-OPSCC patients (95.5%, 95% CI 90.4–100.0; p = 0.002). The PFS for HPV-HNCUP patients was lower (75.6%, 95% CI 54.0–97.2) yet not significantly different to HPV-OPSCC (90.4%, 95% CI 83.5–97.3; p = 0.067). Conclusions: The results presented demonstrate a significant reduced OS and DSS for HPV-HNCUP patients. Accordingly, in our study HPV-HNCUP and HPV-OPSCC are two different entities with a different oncological outcome.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Cancer of unknown primary; Head and neck cancer; HPV-HNCUP; HPV-OPSCC; Neck dissection; Oropharyngeal cancer

Advance directives in patients with head and neck cancer - status quo and factors influencing their creation - Allner, Moritz; Gostian, Magdalena; Rupp, Robin; Allner, Clarissa; Mantsopoulos, Konstantinos; Ostgathe, Christoph; Iro, Heinrich; Hecht, Markus; Gostian, Antoniu-Oreste; Balk, Matthias (BMC Palliative Care, 2022)
Background: Advance Care Planning including living wills and durable powers of attorney for healthcare is a highly relevant topic aiming to increase patient autonomy and reduce medical overtreatment. Data from patients with head and neck cancer (HNC) are not currently available. The main objective of this study was to survey the frequency of advance directives (AD) in patients with head and neck cancer. Methods: In this single center cross-sectional study, we evaluated patients during their regular follow-up consultations at Germany’s largest tertiary referral center for head and neck cancer, regarding the frequency, characteristics, and influencing factors for the creation of advance directives using a questionnaire tailored to our cohort. The advance directives included living wills, durable powers of attorney for healthcare, and combined directives. Results: Four hundred and forty-six patients were surveyed from 07/01/2019 to 12/31/2019 (response rate = 68.9%). The mean age was 62.4 years (SD 11.9), 26.9% were women (n = 120). 46.4% of patients (n = 207) reported having authored at least one advance directive. These documents included 16 durable powers of attorney for healthcare (3.6%), 75 living wills (16.8%), and 116 combined directives (26.0%). In multivariate regression analysis, older age (OR ≤ 0.396, 95% CI 0.181–0.868; p = 0.021), regular medication (OR = 1.896, 95% CI 1.029–3.494; p = 0.040), and the marital status (“married”: OR = 2.574, 95% CI 1.142–5.802; p = 0.023; and “permanent partnership”: OR = 6.900, 95% CI 1.312–36.295; p = 0.023) emerged as significant factors increasing the likelihood of having an advance directive. In contrast, the stage of disease, the therapeutic regimen, the ECOG status, and the time from initial diagnosis did not correlate with the presence of any type of advance directive. Ninety-one patients (44%) with advance directives created their documents before the initial diagnoses of head and neck cancer. Most patients who decide to draw up an advance directive make the decision themselves or are motivated to do so by their immediate environment. Only 7% of patients (n = 16) actively made a conscious decision not create an advance directive. Conclusion: Less than half of head and neck cancer patients had created an advance directive, and very few patients have made a conscious decision not to do so. Older and comorbid patients who were married or in a permanent partnership had a higher likelihood of having an appropriate document. Advance directives are an essential component in enhancing patient autonomy and allow patients to be treated according to their wishes even when they are unable to consent. Therefore, maximum efforts are advocated to increase the prevalence of advance directives, especially in head and neck cancer patients, whose disease often takes a crisis-like course.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Advance care planning; Advance directive; Head and neck Cancer; Living will; Patient autonomy; Power of attorney for healthcare

A New Immortalized Human Lacrimal Gland Cell Line - Gleixner, Sophie; Zahn, Ingrid; Dietrich, Jana; Singh, Swati; Drobny, Alice; Schneider, Yanni; Schwendner, Raphael; Socher, Eileen; Blavet, Nicolas; Bräuer, Lars; Gostian, Antoniu-Oreste; Balk, Matthias; et al. (Cells, 2024)
The lacrimal gland is crucial for maintaining ocular health by producing the aqueous component of the tear film, which hydrates and nourishes the ocular surface. Decreased production of this component results in dry eye disease, a condition affecting over 250 million people worldwide. However, the scarcity of primary human material for studying its underlying mechanisms and the absence of a cell model for human lacrimal gland epithelial cells present significant challenges. Here, we describe the generation of immortalized human lacrimal gland cell lines through the introduction of an SV40 antigen. We successfully isolated and characterized three cell clones from a female lacrimal gland donor, confirming their epithelial identity through genomic and protein analyses, including PCR, RNAseq, immunofluorescence and cultivation in a 3D spheroid model. Our findings represent a significant advancement, providing improved accessibility to investigate the molecular pathogenesis mechanisms of dry eye disease and potential therapeutic interventions. We identified the expression of typical epithelial cell marker genes and demonstrated the cells’ capability to form 2D cell sheets and 3D spheroids. This establishment of immortalized human lacrimal gland cells with epithelial characteristics holds promise for future comprehensive studies, contributing to a deeper understanding of dry eye disease and its cellular mechanisms.<br
Keywords: lacrimal gland; epithelial cells; immortalized; cell line; dry eye; tears; tear secretion

Cartilaginous bending spring tympanoplasty: a temporal bone study and first clinical results - Rupp, Robin; Schelhorn, Tony; Kniesburges, Stefan; Allner, Moritz; Mantsopoulos, Konstantinos; Iro, Heinrich; Hornung, Joachim; Gostian, Antoniu-Oreste; Balk, Matthias (European Archives of Oto-Rhino-Laryngology, 2022)
Objective: Anchoring grafts for tympanic membrane (TM) reconstruction in anterior and subtotal TM defects is essential to prevent medialisation and can be facilitated by cartilaginous bending spring tympanoplasty (CBST). The purpose of this study was to analyse the impact of spring cartilages on middle ear transfer functions and patient hearing levels. Methods: In six fresh-frozen human temporal bones a cartilage graft (measuring 6 × 2 mm with a thickness of 0.1–0.2 mm) was formed into a ‘U’-shaped bending spring, to be placed between the medial tympanic wall and the tympanic underlay grafts. The stapes velocity for excitation by exponential sweeps from 400 to 10,000 Hz was measured with a laser Doppler vibrometer. The resulting middle ear transfer functions were compared with the reconstructed middle ear. For clinical evaluation, 23 ears in 21 patients with chronic otitis media and an intact ossicular chain were operated using CBST. At each follow-up visit, the patients underwent pure-tone audiometry and the Freiburg monosyllabic speech test at a presentation level of 65 dB SPL for the word recognition score (WRS). Results: The measured stapes velocities at one-third octave midband frequencies averaged 3.56 × 10–2 ± 9.46 × 10–3 (mm/s/Pa) compared to 3.06 × 10–2 ± 6.86 × 10–3 (mm/s/Pa) with the bending and underlay cartilage in place (p = 0.319; r = 0.32). The bending spring tympanoplasty reduced the transfer function by 1.41 ± 0.98 dB on average. In the clinical part of the study, the graft success rate was 96% (22 out of 23 patients) after a mean follow-up of 5.8 ± 2.4 months (min. 3.5 months, max. 12.0 months). The air–bone gap improved significantly by 6.2 dB (± 6.6 dB; p < 0.001; r = 0.69), as well as the WRS from 61.8 ± 33.3% preoperatively to 80.0 ± 20.9% postoperatively (p = 0.031; r = 0.35). Conclusion: Experimental data as well as initial clinical results suggest that CBST is an effective method for reconstructing anterior or subtotal defects of the tympanic membrane with satisfactory audiologic results and graft success rates comparable to previously described methods. It can, therefore, be added to the arsenal of tympanoplasty techniques for anterior and subtotal TM perforations.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Anterior tympanic membrane defect; Chronic otitis media; Laser Doppler vibrometry; Middle ear transfer function; Tympanoplasty

Case-tailored indicated extracapsular dissection versus “one-size-fits-all” nerve dissection: Has the bet been won? - Mantsopoulos, Konstantinos; Gehrking, Mika; Thimsen, Vivian; Sievert, Matti; Müller, Sarina Katrin; Rupp, Robin; Balk, Matthias; Gostian, Antoniu-Oreste; Koch, Michael; Iro, Heinrich (American Journal of Otolaryngology, 2024)
Objective: The aim of the study was to trace the development of surgical therapy in a large cohort, examine its changes at one single institution that has been specializing in salivary gland pathologies over the last 22 years, and to determine the extent to which a possible shift in the surgical therapy of parotid benign tumors towards less radical methods was correlated with a change in the incidence of facial palsy and Frey's syndrome. Study design: Retrospective clinical study. Methods: A retrospective evaluation of the records of all patients treated for benign parotid tumors at a tertiary referral center between 2000 and 2022 was carried out. Surgical methods were classified into four groups: extracapsular dissection, partial superficial parotidectomy, superficial parotidectomy and complete parotidectomy. Results: A total of 4037 patients were included in the study. Our analysis demonstrated an increase in the total number of parotidectomies for benign lesions from 71 (2000) to 298 (2022), mostly due to the increase in extracapsular dissections (from 9 to 212). The increased performance of less radical surgery was associated with a significantly decreased incidence of perioperative complications. Conclusions: Our study showed that the increased performance of less radical surgery was associated with better functional outcomes over the years.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Extracapsular dissection; Facial nerve; Fistula; Frey's syndrome; Paresis; Parotid gland; Parotidectomy

Chronic hearing loss turns out being a calcified chondroid mesenchymal neoplasm with FN1::FGFR2 fusion - Bauerschmitz, Leonard; Agaimy, Abbas; Eckstein, Markus; Balk, Matthias; Iro, Heinrich; Schleder, Stephan; Schlaffer, Sven-Martin; Gostian, Antoniu-Oreste (European Archives of Oto-Rhino-Laryngology, 2024)
A 53 year old female presented with a six-year history of right-sided slow deterioration in hearing and a feeling of pressure in the right ear. The patient had not experienced any pain but reported some paresthesia of the right half of the tongue, whereas no further other cranial nerve deficits were evident. The otoscopy was unremarkable as well as the rest of the clinical ENT examination except for a slight asymptomatic swelling of the right cheek. Imaging findings showed an expansive tumor infiltrating and destroying the right lateral skull base. The tumor was partially composed of cystic/regressive lesions with high contrast media uptake. The tumor had high-signal intensity with water-sensitive sequences (T2w) and was hypointense on T1w images. We performed a tumor resection via a transparotideal-infratemporal approach. Histologically, the tumor was composed of granular variably calcified chondroid matrix with extensive regressive changes and granulation-like tissue reaction associated with calcinosis and crystal deposition. Molecular analysis of the tumor via the TruSight- RNA-Fusion panel detected a fusion involving FN1::FGFR2, consistent with “calcified chondroid mesenchymal neoplasm” (CCMN), a rare tumor entity recently defined by Liu et al 2021. In regular follow-up care no residual tumor has been detected in imaging studies (MRI and CT) within 2 years and 4 months. The biology and consequently the radio sensitivity cannot be defined precisely since long term results are missing due to the first description of this entity in 2021. As a consequence, surgical resection is recommended as the treatment of choice. Thorough clinical and radiological follow-up is mandatory as local recurrences are to be expected due to the infiltrative behavior. In case of a loco regional recurrence the fusion with FGFR2 may represent a therapeutic option for a targeted therapy on molecular level.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Calcified chondroid mesenchymal neoplasm; Calcifying aponeurotic fibroma; CCMN; Chondrobastoma; Chondroma; Chondrosarcoma; Chordoma; FGF23; FGFR1; FGFR2; FN1; Ossifying fibromyxoid tumor; Phosphaturic mesenchymal tumors; PMT; Skull base tumor; TEK; Temporomandibular Joint; Tenosynovial giant cell tumor; TruSight-RNA-Fusion panel

Deep Learning and Registration-Based Mapping for Analyzing the Distribution of Nodal Metastases in Head and Neck Cancer Cohorts: Informing Optimal Radiotherapy Target Volume Design - Weissmann, Thomas; Mansoorian, Sina; May, Matthias; Lettmaier, Sebastian; Höfler, Daniel; Deloch, Lisa; Speer, Stefan; Balk, Matthias; Frey, Benjamin; Gaipl, Udo; Bert, Christoph; Distel, Luitpold; et al. (Cancers, 2023)
We introduce a deep-learning- and a registration-based method for automatically analyzing the spatial distribution of nodal metastases (LNs) in head and neck (H/N) cancer cohorts to inform radiotherapy (RT) target volume design. The two methods are evaluated in a cohort of 193 H/N patients/planning CTs with a total of 449 LNs. In the deep learning method, a previously developed nnU-Net 3D/2D ensemble model is used to autosegment 20 H/N levels, with each LN subsequently being algorithmically assigned to the closest-level autosegmentation. In the nonrigid-registration-based mapping method, LNs are mapped into a calculated template CT representing the cohort-average patient anatomy, and kernel density estimation is employed to estimate the underlying average 3D-LN probability distribution allowing for analysis and visualization without prespecified level definitions. Multireader assessment by three radio-oncologists with majority voting was used to evaluate the deep learning method and obtain the ground-truth distribution. For the mapping technique, the proportion of LNs predicted by the 3D probability distribution for each level was calculated and compared to the deep learning and ground-truth distributions. As determined by a multireader review with majority voting, the deep learning method correctly categorized all 449 LNs to their respective levels. Level 2 showed the highest LN involvement (59.0%). The level involvement predicted by the mapping technique was consistent with the ground-truth distribution (p for difference 0.915). Application of the proposed methods to multicenter cohorts with selected H/N tumor subtypes for informing optimal RT target volume design is promising.<br
Keywords: deep learning; artificial intelligence; nodal metastasis; head and neck cancer; radiotherapy; target volume design; atlas; mapping; autosegmentation; lymph node level classification

Defining intra-tumoral and systemic immune biomarkers for locally advanced head-and-neck cancer – detailed protocol of a prospective, observatory multicenter trial (ImmunBioKHT) and first results of the immunophenotyping of the patients’ peripheral blood - Donaubauer, Anna-Jasmina; Frey, Benjamin; Weber, Manuel; Allner, Moritz; Vogl, Christoph; Almajali, Omar; Kuczera, Lukas; Tamse, Henriette; Balk, Matthias; Müller-Hübner, Sarina Katrin Ursel; Eckstein, Markus; Zülch, Lilli; et al. (Frontiers in Oncology, 2024)
The approval and effectiveness of immune checkpoint inhibitors in head-and-neck squamous cell carcinoma (HNSCC) highlights the role of the immune system in this tumor entity. HNSCCs not only interacts with the immune system in the tumor tissue, but also induce systemic effects that may be additionally influenced by further factors such as the microbiome. Nonetheless, reliable immunological biomarkers that predict treatment response and outcome in HNSCC patients are lacking. The currently available biomarkers are mainly limited to analyses from tumor biopsies, while biomarkers from liquid biopsies, such as peripheral blood are not well-established. Thus, the here presented trial aims to identify interactions of intra-tumoral and systemic immune responses and to define prognostic immune signatures. Consequently, not only samples from the tumor tissue, but also from peripheral blood and the microbiome will be studied/are being evaluated and correlated with the clinical outcome. In this prospective, multi-center trial, 1000 HNSCC patients and 100 patients in the control cohort with non-tumor head-and-neck surgery will be enrolled. The local immune status from of the tumor and the microbiome will be sampled before treatment. In addition, the systemic immune status from peripheral blood will be analyzed before and after surgery and after the adjuvant and definitive radio-chemotherapy (RCT). Clinical baseline characteristics and outcome will additionally be collected. Data mining and modelling approaches will finally be applied to identify interactions of local and systemic immune parameters and to define prognostic immune signatures based on the evaluated immune markers. Approval from the institutional review board of the Friedrich-Alexander-Universität Erlangen-Nürnberg was granted in December 2021 (application number 21-440-B). By now, 150 patients have been enrolled in the intervention cohort. The results will be disseminated to the scientific audience and the general public via presentations at conferences and publication in peer-reviewed journal
CRIS-Team Scopus Importer:2024-10-04
Keywords: HNSCC; immune monitoring; immunological biomarker; liquid biopsy; prospective clinical trial

Diagnosing complications following cochlear implantation using transcutaneous ultrasound - Rupp, Robin; Thimsen, Vivian; Balk, Matthias; Müller-Hübner, Sarina Katrin Ursel; Sievert, Matti; Mantsopoulos, Konstantinos; Hoppe, Ulrich; Hornung, Joachim; Iro, Heinrich; Gostian, Antoniu-Oreste (European Archives of Oto-Rhino-Laryngology, 2021)
Purpose: The aim of this study was to investigate the feasibility and reliability of transcutaneous ultrasound for the detection of complications after cochlear implantation. Methods: In a single center retrospective cohort study, 115 consecutive cases of suspected complications after cochlear implantation (intervention group) were examined. The rate of pathologic ultrasound findings for specific leading symptoms and diagnoses was compared to a control group comprising twenty consecutive cochlear implants in symptom-free patients. Results: Diagnostic ultrasound showed distinctly more pathologic findings in the intervention group (n = 67; 58.3%; p < 0.001) compared to the control group (n = 1; 5%). Ultrasound revealed significantly more pathologic findings in haematoma or seroma around the implant (n = 17; 100%; p < 0.001; ϕ = 0.94) and magnet dislocation (n = 44; 97.7%; p < 0.001; ϕ = 0.92) confirmed by a strong effect. Ultrasound examination showed a medium to high effect size in patients presenting with local infections (n = 3; 21.4%; p = 0.283; ϕ = 0.25) and skin flap oedema (n = 2; 50%; p = 0.061; ϕ = 0.51). In contrast, ultrasound examinations displayed a low effect size in undefined cephalgia (0%; p = 0.444; ϕ = 0.17) and device malfunction or failure (0%; p > 0.999; ϕ = 0.13). Conclusion: Transcutaneous ultrasound can be advocated as a feasible and effective method in the diagnostic work-up of magnet dislocation and haematoma or seroma around the implant following cochlear implantation. Contrary, ultrasound findings can be expected to be inconspicuous in patients presenting with undefined cephalgia and device malfunction or failure.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Cochlear implant; Diagnostic sonography; Haematoma; Magnet dislocation; Seroma; Transcutaneous ultrasound

EAONO/JOS classification for acquired cholesteatoma: evaluating the impact of the number of affected sites on treatment and outcomes - Renner, Beatrix; de Vasconcelos Craveiro, Antonio; Balk, Matthias; Allner, Moritz; Sievert, Matti; Müller, Sarina Katrin; Mantsopoulos, Konstantinos; Iro, Heinrich; Rupp, Robin; Hornung, Joachim; Gostian, Antoniu-Oreste (European Archives of Oto-Rhino-Laryngology, 2023)
Purpose: The European and Japanese system for cholesteatoma classification proposed an anatomical differentiation in five sites. In stage I disease, one site would be affected and in stage II, two to five. We tested the significance of this differentiation by analyzing the influence of the number of affected sites on residual disease, hearing ability and surgical complexity. Methods: Cases of acquired cholesteatoma treated at a single tertiary referral center between 2010-01-01 and 2019-07-31 were retrospectively analyzed. Residual disease was determined according to the system. The air–bone gap mean of 0.5, 1, 2, 3 kHz (ABG) and its change with surgery served as hearing outcome. The surgical complexity was estimated regarding the Wullstein’s tympanoplasty classification and the procedure approach (transcanal, canal up/down). Results: 513 ears (431 patients) were followed-up during 21.6 ± 21.5 months. 107 (20.9%) ears had one site affected, 130 (25.3%) two, 157 (30.6%) three, 72 (14.0%) four and 47 (9.2%) five. An increasing number of affected sites resulted in higher residual rates (9.4–21.3%, p = 0.008) and surgical complexity, as well poorer ABG (preoperative 14.1 to 25.3 dB, postoperative 11.3–16.8 dB, p < 0.001). These differences existed between the means of cases of stage I and II, but also when only considering ears with stage II classification. Conclusion: The data showed statistically significant differences when comparing the averages of ears with two to five affected sites, questioning the pertinence of the differentiation between stages I and II.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Cholesteatoma; EAONO/JOS classification; Tympanoplasty

Exosomal Serum Biomarkers as Predictors for Laryngeal Carcinoma † - Schuster, Julius; Wendler, Olaf; Pesold, Vanessa-Vivien; Koch, Michael; Sievert, Matti; Balk, Matthias; Rupp, Robin; Müller, Sarina Katrin (Cancers, 2024)
Background: The lack of screening methods for LSCC is a critical issue, as treatment options and the treatment outcome greatly depend on the stage of LSCC at initial diagnosis. Therefore, the objective of this study was to identify potential exosomal serum biomarkers that can diagnose LSCC and distinguish between early- and late-stage disease. Methods: A multiplexed proteomic array was used to identify differentially expressed proteins in exosomes isolated from the serum samples of LSCC patients compared to the control group (septorhinoplasty, SRP). The most promising proteins for diagnosis and differentiation were calculated using biostatistical methods and were validated by immunohistochemistry (IHC), Western blots (WB), and ELISA. Results: Exosomal insulin-like growth factor binding protein 7 (IGFBP7) and Annexin A1 (ANXA1) were the most promising exosomal biomarkers for distinguishing between control and LSCC patients and also between different stages of LSCC (fold change up to 15.9, p < 0.001 for all). Conclusion: The identified proteins represent potentially novel non-invasive biomarkers. However, these results need to be validated in larger cohorts with a long-term follow-up. Exosomal biomarkers show a superior signal-to-noise ratio compared to whole serum and may therefore be an important tool for non-invasive biomarker profiling for laryngeal carcinoma in the future.
CRIS-Team Scopus Importer:2024-06-21
Keywords: ANXA1; biomarker; exosomes; IGFBP7; liquid-biopsy; LSCC

Factors Influencing the Outcome of Head and Neck Cancer of Unknown Primary (HNCUP) - Rupp, Robin; Mantsopoulos, Konstantinos; Sievert, Matti; Gostian, Magdalena; Allner, Moritz; Grundtner, Philipp; Eckstein, Markus; Iro, Heinrich; Hecht, Markus; Gostian, Antoniu-Oreste; Balk, Matthias (Journal of Clinical Medicine, 2022)
Background: This study on patients with head and neck cancer of unknown primary (HNCUP) assesses the impact of surgical and non-surgical treatment modalities and the tumour biology on the oncological outcome. Methods: A total of 80 patients with HNCUP (UICC I-IV) were treated with simultaneous neck dissection followed by adjuvant therapy, between 1 January 2007 and 31 March 2020. As the primary objective, the influence of treatment modalities on the overall survival (OS), the disease-specific survival (DSS) and the progression-free survival (PFS) were analysed in terms of cox regression and recursive partitioning. The tumour biology served as secondary objectives. Results: The 5-year OS for the entire cohort was 67.7%, (95% CI: 54.2-81.2%), the 5-year DSS was 82.3% (72.1-92.5%) and the 5-year PFS was 72.8% (61.8-83.8%). Cox regression revealed that patients undergoing adjuvant radiotherapy only had a four times higher risk to die compared to patients receiving chemoradiation therapy (HR = 4.45 (1.40; 14.17), p = 0.012). The development of distant metastases had a significantly negative impact on OS (HR = 8.24 (3.21-21.15), p < 0.001) and DSS (HR = 23.79 (6.32-89.56), p < 0.001). Recursive portioning underlined the negative influence of distant metastases on OS (3.2-fold increase in death probability) and DSS (4.3-fold increase in death probability), while an UICC stage of IVb increased the risk for further progression of the disease by a factor of 2. Conclusions: The presence of distant metastases as well as adjuvant treatment with radiation without concomitant chemotherapy, were among others, significant predictors for the overall survival of HNCUP patients, with distant metastases being the most significant predictor.
CRIS-Team WoS Importer:2022-06-10

Impact of Cancer Localization on Symptom Burden and Quality of Life in Head and Neck Cancers: A Comparative Study - Balk, Matthias; Rak, Atina; Rupp, Robin; Sievert, Matti; Müller-Hübner, Sarina Katrin Ursel; Koch, Michael; Iro, Heinrich; Gostian, Magdalena; Putz, Florian; Weissmann, Thomas; Allner, Moritz; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2024)
Background: Head and neck cancer (HNC) is a critical concern in oncology, with notable disparities in survival rates. While the long-term symptom burden in HNC survivors and its impact on quality of life (QoL) has been explored, there is limited understanding of the influence of cancer localizations on these aspects. This study aims to elucidate the role of cancer localizations in shaping long-term outcomes in HNC patients. Methods: A cross-sectional study was conducted at the University Hospital Erlangen’s Department of Otolaryngology, exploring the impact of cancer localization on symptom burden and QoL in 138 HNC patients using the University of Washington Quality of Life Questionnaire Version 4. Results: In our study of HNC patients, we investigated symptom burden across different cancer localizations, including oral cavity, oropharyngeal, hypopharyngeal, laryngeal, and cancer of unknown primary (CUP). While we found no significant variations in parameters such as pain, appearance, and activity, notable differences emerged in swallowing, speech, and salivation. Patients with oral cavity and laryngeal carcinomas had significantly higher swallowing and salivation scores compared to those with oropharyngeal carcinoma and CUP, while speech-related symptoms were lower for oral cavity and laryngeal carcinoma patients. Importantly, these symptom differences did not significantly impact health-related and overall QoL. These findings emphasize the nuanced interplay between symptomatology and QoL in different HNC cancer localizations. Conclusion: The research highlights significant disparities in post-treatment symptoms across different HNC localizations and underscores the need for personalized treatment and management strategies to address unique challenges associated with each HNC type, ultimately aiming to enhance post-treatment QoL.
CRIS-Team Scopus Importer:2024-11-08
Keywords: advanced-stage cancer; cancer; disease stage; early-stage cancer; follow-up; head and neck cancer; individualized care; patient-reported outcome; physical symptoms; psychological symptoms; quality of life; survivorship; symptom burden

Investigation of locoregional metastatic behavior in low-grade malignant tumors of the parotid gland - Kapsalas, Andreas; Thimsen, Vivian; Varga, Regina; Agaimy, Abbas; Sievert, Matti; Balk, Matthias; Rupp, Robin; Koch, Michael; Iro, Heinrich; Mantsopoulos, Konstantinos (American Journal of Otolaryngology, 2023)
Background: The aim of the study was to investigate primary locoregional metastatic behavior in a large sample of low-grade malignant tumors of the parotid gland following surgical treatment consisting of complete parotidectomy and neck dissection. Methods: The records of all patients treated for low-grade malignant tumors of the parotid gland by complete parotidectomy and neck dissection between 2007 and 2022 were studied retrospectively. Results: 94 patients formed our study sample (50 females, 44 males, female to male ratio: 1.14). The mean age was 59 years (range 15–95 years). The mean number of lymph nodes in the specimen from complete parotidectomy was 3.33 (range: 0–12). The mean number of involved lymph nodes in the parotid gland was 0.05 (range: 0–1). The mean number of lymph nodes in the specimen from the ipsilateral neck dissection was 16.2 (range 4–42). The mean number of involved lymph nodes in the neck dissection specimen was 0.09 (range: 0–2). Comparison of T1-T2 vs. T3-T4 cases revealed no statistically significant difference concerning the tumorous involvement of the lymphatic network (x2 = 0.719, p = 0.396). Conclusion: Low-grade primary malignant tumors of the parotid gland are characterized by an initially low metastatic potential, which justifies conservative forms of surgical treatment.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Low-grade; Malignant tumor; Neck dissection; Parotid gland; Parotidectomy

Limited parotid surgery as sole form of treatment for carefully selected malignant tumours of the parotid gland: Still sufficient on the long-term? - Mantsopoulos, Konstantinos; Thimsen, Vivian; Sievert, Matti; Balk, Matthias; Grundtner, Philipp; Gostian, Antoniu-Oreste; Koch, Michael; Iro, Heinrich (American Journal of Otolaryngology, 2023)
Background: The aim of the study was to investigate the oncological and functional outcome following extracapsular dissection as the sole form of treatment in locally limited low-grade malignant parotid tumours in the long term. Methods: The records of all patients treated for T1-T2 low-grade malignant tumours of the parotid gland solely by means of extracapsular dissection between 2005 and 2017 were studied retrospectively. Results: A total of 16 cases formed our study sample (7 men, 9 women). Their mean age was 50.2 years (21–84 years). Mean follow-up was 107 months (60–201 months). In 6 cases the tumour was an acinic cell carcinoma, in 9 cases a mucoepidermoid carcinoma and in one case a basal cell adenocarcinoma. Regarding the T category, the tumour was Tis in one case, T1 in 12 cases and T2 in three cases. The five-year disease-specific survival rate was 100 %, as was local disease control. Facial nerve function was House-Brackmann grade I without exception. Conclusions: Our study showed very encouraging long-term results following primary extracapsular dissection as the sole surgical therapy for carefully selected low-stage, low-grade, inferiorly located lesions in patients with high compliance. Lay summary: The “one-size-fits-all” strategy of complete parotidectomy with neck dissection might be tantamount to overtreatment by less aggressive cases of parotid cancer. Extracapsular dissection seems to be oncologically sufficient for carefully selected T1-T2 low-grade cases in the long-term in patients with ensured follow-up.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Extracapsular dissection; Facial nerve; Low-grade; Malignant tumour; Parotid gland

Pain management after tonsillectomy—by demand or by-the-clock—is there a difference? - Gostian, Magdalena; Stilkerich, Lisa; Pauly, Anne; Balk, Matthias; Rupp, Robin; Allner, Moritz; Iro, Heinrich; Gostian, Antoniu-Oreste; Waldfahrer, Frank (Ent-Ear Nose & Throat Journal, 2022)
Purpose: To improve pain management after tonsillectomy (TE) by comparing individual analgesic management by demand versus a fixed-scheduled analgesic treatment protocol in a prospective trial. Patients and Methods: Forty consecutive patients received individual pain treatment by demand (control group) followed by 40 patients who were treated by a fixed-scheduled four-staged escalating analgesic protocol (intervention group) after TE. Minimum and maximum pain as well as pain on ambulation (NRS 0-10) on the first postoperative day were defined as primary objectives. Secondary endpoints comprised the analgesic score, treatment-related side effects/pain-associated impairments, wish for more pain medication, and patient satisfaction. Patients were surveyed using the standardized and validated “Quality Improvement in Postoperative Pain Treatment” (QUIPS) questionnaire. Results: Patients of the control group reported comparable minimum (2.03 ± 1.42 vs 2.38 ± 1.79, P = 0.337, r = 0.110) and maximum pain (6.65 ± 2.10 vs 6.93 ± 1.86, P = 0.536, r = 0.07) and pain on ambulation (4.73 ± 2.26 vs 5.18 ± 2.19, P = 0.370, r = 0.10) compared to the intervention group. Patients in both groups were comparably well satisfied with the pain treatment (7.53 ± 2.40 vs 7.73 ± 2.30, P = 0.704, r = 0.04), experienced similar side effects and functional impairments (P > 0.050, Φ < 0.3), and did not ask for much more analgesic medication (P = 0.152, Φ = 0.160). Conclusion: Pain control following TE was not distinctly affected by applying a fixed-scheduled analgesic treatment protocol compared to individual analgesic therapy. In conclusion, analgesic treatment after TE remains unsatisfying. Consequently, further efforts are needed to achieve a standardized and effective approach to the underlying pathophysiological causes of pain following TE.
CRIS-Team Scopus Importer:2022-08-05
Keywords: patient reported outcome measure; postoperative pain; quality management; QUIPS

Perioperative anticoagulation in free microvascular flaps – a comparison of different prophylactic regimes in oncologic reconstructive surgery - Tamse, Henriette; Koch, Michael; Müller, Sarina Katrin; Gostian, Antoniu-Oreste; Balk, Matthias; Rupp, Robin; Allner, Moritz; Iro, Heinrich; Sievert, Matti (European Review for Medical and Pharmacological Sciences, 2024)
OBJECTIVE: Free tissue transfer has an established place in oncologic head and neck surgery. However, the necessity and specific regimen of perioperative thromboprophylaxis remain controversial. Here, the risk of postoperative hemorrhage contrasts with vascular pedicle thrombosis and graft loss. This work compares three different heparin protocols (AC) with regard to postoperative complications. PATIENTS AND METHODS: A retrospective analysis of our free flap transplants between 2004 and 2023 was conducted. Inclusion criteria were thromboprophylaxis with (A) 500 IU/h unfractionated heparin (UFH), (B) low-molecular-weight heparin (LMWH) once daily, and (C) LMWH once daily with additional immediate preoperative administration. Primary endpoints were the incidence of postoperative bleeding and hematoma and the appearance of flap thrombosis. RESULTS: We evaluated 355 cases, 87 in group A, 179 in group B, and in group C 89 patients. Overall, postoperative bleeding occurred in 8.7% of patients, and 83% underwent hemostasis under intubation anesthesia, with no significant difference between groups (p = 0.784). Hematoma formation requiring revision was found in 3.7% of patients (p = 0.660). We identified postoperative hematoma as a significant influencing factor for venous pedicle thrombosis (OR 3.602; p = 0.001). Venous and arterial flap thrombosis in the graft vessel showed no difference between the groups (p = 0.745 and p = 0.128). CONCLUSIONS: The three anticoagulation regimens appear to be equivalent therapy for the prevention of thrombosis without significant differences in postoperative bleeding. The use of LMWH with additional preoperative administration can, therefore, be administered in free flap reconstruction.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Anticoagulation; Bleeding; Flap thrombosis; Free flap; Hematoma; Heparin; Microvascular reconstruction

Postoperative pain after parotid surgery—comparison between superficial/total parotidectomy and extracapsular dissection: a prospective observational study - Jansen, Valentin; Gostian, Antoniu-Oreste; Allner, Moritz; Balk, Matthias; Rupp, Robin; Iro, Heinrich; Hecht, Markus; Gostian, Magdalena (European Archives of Oto-Rhino-Laryngology, 2024)
Purpose: To evaluate postoperative pain and discomfort after parotid surgery with regard to different surgical approaches. Methods: This clinical study was carried out at a single tertiary referral center (2021–2022) and included 2 groups of adult patients (mean age 56.6 ± 12.7 vs. 53.4 ± 14.1 years) following elective parotid surgery due to a parotid tumor of any entity. The first group (SP/TP group) consisted of 31 patients after superficial parotidectomy (SP) or total parotidectomy (TP) (n = 31). The second group (ECD group) included all patients who had undergone extracapsular dissection (ECD) (n = 51). Primary endpoints comprised pain on ambulation as well as maximum and minimum pain (NRS 0–10) on the first three postoperative days (PODs). A neuropathic pain component (evaluated on POD 1 and 3), the analgesic score (collected from the patient file on POD 1–3), treatment-related side-effects/pain-associated impairments, and patient satisfaction (all measured on the 1st POD) were defined as secondary endpoints. Patients were surveyed using the standardized and validated “Quality Improvement in Postoperative Pain Treatment” (QUIPS) questionnaire and the painDETECT® questionnaire. Comparisons were performed using independent t tests, Wilcoxon tests, and χ2 tests, and the respective effect sizes were calculated. Results: Looking at the first postoperative day, patients of both groups (SP/TP vs. ECD) reported comparable pain on ambulation (2.8 ± 2.0 vs. 2.6 ± 1.8; p = 0.628, r = 0.063), maximum (3.5 ± 2.2 vs. 3.5 ± 2.3; p = 0.992, r = 0.002) and minimum pain (1.1 ± 1.04 vs. 1.0 ± 1.2; p = 0.206, r = 0.157). Furthermore, there were no significant differences in pain-related restrictions or pain medication requirement. The patients in both groups were equally satisfied with their pain therapy (p = 0.282, R = 0.135). The sum score of the painDETECT® questionnaire delivered clearly negative (< 12) results on average (POD1: 6.81; POD3: 6.59); no significant difference between the groups was found (p = 0.991, R2 <.001). Conclusion: Neither surgical technique on the parotid gland was significantly superior to the other in terms of postoperative pain perception. Overall, postoperative pain can be classified as mild to moderate following parotid surgery. A neuropathic pain component could be excluded for the acute postoperative phase. Trial registration: The study was registered in the German Registry for Clinical Studies (DRKS) (application No.: DRKS00016520).
CRIS-Team Scopus Importer:2024-10-11
Keywords: Extracapsular dissection; Pain management; Parotid surgery; Patient-reported outcome measure; Postoperative pain; Quality management; QUIPS

Precautionary documents in patients with head and neck cancer - status quo and factors influencing their creation - Allner, Moritz; Gostian, M.; Balk, Matthias; Rupp, Robin; Hecht, Markus; Ostgathe, Christoph; Müller, Sarina Katrin; Iro, Heinrich; Gostian, Antoniu-Oreste (ORAL ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-07-16

Relevance of the time interval between surgery and adjuvant radio (chemo) therapy in HPV-negative and advanced head and neck carcinoma of unknown primary (CUP) - Balk, Matthias; Rupp, Robin; Mantsopoulos, Konstantinos; Allner, Moritz; Grundtner, Philipp; Müller-Hübner, Sarina Katrin Ursel; Traxdorf, Maximilian; Eckstein, Markus; Speer, Stefan; Semrau, Sabine; Fietkau, Rainer; Iro, Heinrich; et al. (BMC Cancer, 2021)
Introduction In contrast to head and neck squamous cell carcinoma (HNSCC), the effect of treatment duration in HNSCC-CUP has not been thoroughly investigated. Thus, this study aimed to assess the impact of the time interval between surgery and adjuvant therapy on the oncologic outcome, in particular the 5-year overall survival rate (OS), in advanced stage, HPV-negative CUPs at a tertiary referral hospital. 5-year disease specific survival rate (DSS) and progression free survival rate (PFS) are defined as secondary objectives. Material and methods Between January 1st, 2007, and March 31st, 2020 a total of 131 patients with CUP were treated. Out of these, 59 patients with a confirmed negative p16 analysis were referred to a so-called CUP-panendoscopy with simultaneous unilateral neck dissection followed by adjuvant therapy. The cut-off between tumor removal and delivery of adjuvant therapy was set at the median, i.e. patients receiving adjuvant therapy below or above the median time interval. Results Depending on the median time interval of 55 days (d) (95% CI 51.42-84.52), 30 patients received adjuvant therapy within 55 d (mean 41.69 d, SD = 9.03) after surgery in contrast to 29 patients at least after 55 d (mean 73.21 d, SD = 19.16). All patients involved in the study were diagnosed in advanced tumor stages UICC III (n = 4; 6.8%), IVA (n = 27; 45.8%) and IVB (n = 28; 47.5%). Every patient was treated with curative neck dissection. Adjuvant chemo (immune) radiation was performed in 55 patients (93.2%), 4 patients (6.8%) underwent adjuvant radiation only. The mean follow-up time was 43.6 months (SD = 36.7 months). The 5-year OS rate for all patients involved was 71% (95% CI 0.55-0.86). For those patients receiving adjuvant therapy within 55 d (77, 95% CI 0.48-1.06) the OS rate was higher, yet not significantly different from those with delayed treatment (64, 95% CI 0.42-0.80; X-(1)(2) = 1.16, p = 0.281). Regarding all patients, the 5-year DSS rate was 86% (95% CI 0.75-0.96). Patients submitted to adjuvant treatment in less than 55 d the DSS rate was 95% (95% CI 0.89-1.01) compared to patients submitted to adjuvant treatment equal or later than 55 d (76% (95% CI 0.57-0.95; X-(1)(2) = 2.32, p = 0.128). The 5-year PFS rate of the entire cohort was 72% (95% CI 0.59-0.85). In the group < 55 d the PFS rate was 78% (95% CI 0.63-0.94) and thus not significantly different from 65% (95% CI 0.45-0.85) of the group >= 55 d; (X-(1)(2) = 0.29, p = 0.589). Conclusions The results presented suggest that the oncologic outcome of patients with advanced, HPV-negative CUP of the head and neck was not significantly affected by a prolonged period between surgery and adjuvant therapy. Nevertheless, oncologic outcome tends to be superior for early adjuvant therapy.
CRIS-Team WoS Importer:2021-12-03

Relevance of the time interval between surgery and adjuvant radio (chemo) therapy in HPV-negative and advanced head and neck carcinoma of unknown primary (CUP) - Balk, Matthias; Rupp, Robin; Mantsopoulos, Konstantinos; Allner, Moritz; Grundtner, Philipp; Müller, Sarina Katrin; Traxdorf, Maximilian; Eckstein, Markus; Speer, Stefan; Semrau, Sabine; Fietkau, Rainer; Iro, Heinrich; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Results of contralateral anastomosis of microvascular free flaps in head and neck reconstruction - Gschoßmann, Juliane; Balk, Matthias; Rupp, Robin; Müller-Hübner, Sarina Katrin Ursel; Allner, Moritz; Sievert, Matti; Mantsopoulos, Konstantinos; Koch, Michael; Iro, Heinrich; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2022)
Objectives: Despite various solutions to the issue of ipsilateral vessel-depleted neck in microvascular head and neck reconstruction, concrete data on its safety and implementation are scarce. This paper focuses on the feasibility and success rates of contralateral anastomosis in free flap reconstruction in the head and neck region. Methods: This single-center retrospective study at a tertiary referral center includes all patients who underwent free flap reconstruction of the head and neck with contralateral anastomosis between January 1st, 2007 and February 28th, 2021. Primary objectives were frequency, success, and flap-associated complication rates. Secondary objectives were recipient vessels and flap type. Results: Of 318 patients who underwent microvascular reconstruction, anastomosis was performed on the contralateral side of the neck in 32 patients (10.0%). Recipient vessels involved mainly the superior thyroid artery (74.2%; n = 23) and the facial vein (51.1%; n = 23). Thirty patients (93.8%) received a radial forearm free flap. Flap-associated complications occurred in 12.5% of included cases (n = 4): one partial flap necrosis (3.1%), one anastomotic insufficiency (3.1%), one venous thrombosis of the microvascular pedicle (3.1%), and one wound dehiscence (3.1%). All of these complications were resolved without complete flap loss. Conclusion: This study demonstrates that contralateral anastomosis is a successful and safe option in microvascular head and neck reconstruction, especially using a radial forearm free flap. Thus, anastomosing to the contralateral side of the neck can be advocated as a valuable option in the ipsilateral vessel-depleted neck.
CRIS-Team Scopus Importer:2022-07-15
Keywords: contralateral anastomosis; free flaps; head and neck cancer; microvascular reconstruction; recipient vessels; vessel-depleted neck

Risk of magnetic resonance imaging-induced magnet dislocation for different types of cochlear implants: a single-center retrospective study - Rupp, Robin; Balk, Matthias; Sievert, Matti; Leibl, Victoria; Schleder, Stephan; Allner, Moritz; Iro, Heinrich; Hoppe, Ulrich; Hornung, Joachim; Gostian, Antoniu-Oreste (Journal of Otolaryngology-Head & Neck Surgery, 2023)
Background: When performing magnetic resonance imaging (MRI) in patients with a cochlear implant (CI), complication rates vary widely in the literature. The primary objective of this retrospective study was to determine the prevalence of complications, in particular magnet dislocation, in patients with CI undergoing 1.5 Tesla (T) MRI. As a secondary objective, the prevalence of magnet dislocation for specific cochlear implant device types was elaborated. Methods: In a single-center retrospective study, all patients with a cochlear implant presenting for an MRI examination at 1.5 T at our institution between January 1st, 2010 and December 31st, 2020 were included. Implants with axial and diametrical magnets were included in the study. MRI safety measures were applied before imaging. The prevalence of complications was evaluated. Magnet dislocation rates were calculated for device types with at least 20 MRI exposures. Results: During the study period, 196 MRI examinations were performed in a total of 128 patients, accounting for 149 different implants (21 implanted bilaterally) with a total of 231 implant exposures to MRI (average 1.69 ± 1.57; min. 1, max. 12). Complications were reported in 50 out of 231 cochlear implant exposures (21.6%). Magnet dislocation occurred in a total of 27 cases (11.7%). Dislocation rates were 29.6% for the Cochlear® CI500 series (24 dislocations from 81 exposures), 1.1% for the Cochlear® CI24RE series (1 from 87) and 0% for the MED-EL® Synchrony (0 from 36). The dislocation rate for the CI500 was significantly higher than for the CI24RE (χ2(1) = 26.86; p < 0.001; ϕ = 0.40) or the Synchrony (χ2(1) = 13.42; p < 0.001; ϕ = 0.34). Conclusions: For 1.5 T MRI, the risk of magnet dislocation ranges from 0 to 29.6% and depends on the CI device type. Implants with a diametrical magnet can be considered potentially MRI-safe, whereas in CIs with axial magnets, the CI500 is at high risk of magnet dislocation. Therefore, apart from a strict indication for an MRI and adherence to safety protocols, post-MRI follow-up examination to rule out magnet dislocation is recommended. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-05-05
Keywords: CI24RE; CI500; Cochlear implant; Complication; Magnet dislocation; Magnet repositioning; Magnetic resonance imaging; Synchrony

Risk stratification of thyroid nodules: Assessing the suitability of ChatGPT for text-based analysis - Sievert, Matti; Conrad, Olaf; Müller, Sarina Katrin; Rupp, Robin; Balk, Matthias; Richter, Daniel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (American Journal of Otolaryngology, 2024)
Purpose: Accurate risk stratification of thyroid nodules is essential for optimal patient management. This study aimed to assess the suitability of ChatGPT for risk stratification of thyroid nodules using a text-based evaluation. Methods: A dataset was compiled comprising 50 anonymized clinical reports and associated risk assessments for thyroid nodules. The Chat Generative Pre-trained Transformer (ChatGPT) was used to classify sonographic patterns in accordance with the Thyroid Imaging Reporting and Data System (TI-RADS). The model's performance was assessed using various criteria, including sensitivity, specificity, and accuracy. A comparative analysis was conducted, evaluating the model against investigator-based risk stratification as well as histology. Results: With an overall agreement rate of 42 % in comparison with examiner-based evaluation (TI-RADS 1–5), the results show that ChatGPT has moderate potential for predicting the risk of malignancy in thyroid nodules using text-based reports. The chatbot model achieved a sensitivity of 86.7 %, a specificity of 10.7 %, and an overall accuracy of 68 % when distinguishing between low-risk (TI-RADS 2 and 3) and high-risk (TI-RADS 4 and 5) categories. Interrater reliability was calculated with a Cohen's kappa of 0.686. Conclusion: This study highlights the potential of ChatGPT in assisting clinicians with risk stratification of thyroid nodules. The results suggest that ChatGPT can facilitate personalized treatment decisions, although the agreement rate is still low. Further research and validation studies are necessary to establish the clinical applicability and generalizability of ChatGPT in routine practice. The integration of ChatGPT into clinical workflows has the potential to enhance thyroid nodule risk assessment and improve patient care.
CRIS-Team Scopus Importer:2024-01-19
Keywords: AI; ChatGPT; Risk stratification; Thyroid nodules; Ultrasound

Surgical Versus Noninvasive Manual Repositioning After Cochlear Implant Partial Magnet Dislocation - Rupp, Robin; Balk, Matthias; Allner, Moritz; Sievert, Matti; Müller, Sarina Katrin; Hoppe, Ulrich; Hornung, Joachim; Iro, Heinrich; Gostian, Antoniu Oreste (Ent-Ear Nose & Throat Journal, 2023)
Objectives: To compare surgical magnet repositioning (SMR) and noninvasive manual magnet repositioning (MMR) as treatments for partial magnet dislocation (PMD) of the internal magnet in a cochlear implant (CI) caused by magnetic resonance imaging (MRI). The primary objective was the success rate, while the secondary objectives were total postinterventional CI downtime and complications. Methods: This single-center retrospective study was conducted at a tertiary referral medical center. Patients with CI treated for PMD between January 1, 2007 and September 30, 2022 were included. SMR served as primary treatment until June 2019 and as secondary treatment after the introduction of MMR. Results: A total of 51 cases of PMD were observed in 42 patients and 43 devices (18 ♀; 24 ♂; 12 with bilateral CI). MMR was performed successfully in 19 out of 20 cases (95%), while 32 cases were managed successfully by SMR. The median age at first magnet repositioning was 53.8 years (minimum 19 years, maximum 93 years). When MMR was performed, the mean time from diagnosis to treatment (0.5 ± 1.5 days vs 9.8 ± 7.6 days; P <.01), the mean time from repositioning to CI reactivation (1.4 ± 4.3 days vs 13.1 ± 6.7 days; P <.01), and the mean total CI downtime (1.9 ± 4.8 days vs 22.9 ± 11.9 days; P <.01) were significantly shorter compared to SMR. Significantly fewer complications were experienced with MMR [n = 0 (0%) vs n = 8 (25%); P =.04]. Conclusion: In case of PMD caused by MRI, noninvasive MMR shows a high success rate with a shorter total CI downtime as well as a lower complication rate compared to SMR. Therefore, MMR should be considered as first line treatment with SMR as a second option in case of failure.
CRIS-Team Scopus Importer:2024-12-16
Keywords: CI500; cochlear implant; complication; magnet dislocation; magnet repositioning; magnetic resonance imaging; manual maneuver

Symptom Burden and Quality of Life in Long-Term Survivors with Head and Neck Cancer - Gostian, Magdalena; Allner, Moritz; Rak, Atina; Balk, Matthias; Rupp, Robin; Ostgathe, Christoph; Mantsopoulos, Konstantinos; Sievert, Matti; Iro, Heinrich; Hecht, Markus; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2024)
Objectives: In this study, long-term survivors of head and neck cancer (HNC) were evaluated regarding their symptom burden and quality of life (QoL). Methods: This prospective study was performed during the regular follow-up consultations at one of Germany’s largest tertiary referral centers for HNC. The assessment included demographic, clinical, and oncological data, as well as the MIDOS(2) and the University of Washington Quality of Life Questionnaire (UW QoL) questionnaires. Patients were subdivided based on their disease stage, that is, early cancer stages (UICC I/II) and advanced cancer stages UICC (III/IV). Results: Between January 1, 2019 and December 31, 2019, 212 HNC patients with a mean follow-up of 46.36 ± 43.64 months were included (120 patients UICC stage I/II (22.5% female, mean age 61.93 ± 12.38 years) versus 92 patients UICC stage III/IV (25.0% female, mean age 63.73 ± 11.74 years)). For all patients evaluated (UICC I/II versus III/IV), the three most common symptoms were tiredness (47.5 vs 60.9%, P =.073, r =.123), anxiety (35.8 vs 32.6%, P =.624, phi =.034) and drowsiness (35.0 vs 44.6%, P =.157, phi =.097). Patients diagnosed with UICC III/IV stages reported loss of appetite significantly more frequently and with a high level of severity (15.0 vs 32.6%, P =.002, phi =.157; 0.23 ± 0.60 vs 0.47 ± 0.78, P =.003, r =.203). The overall symptom burden was low with a severity sum score (min 0-max 30) of 3.04 ± 3.29 versus 3.58 ± 3.38 (P =.143, r =.100). All patients rated their QoL as good (65.67 ± 20.93 vs 59.56 ± 22.00, P =.043, r =.139). Conclusion: The overall symptom burden of long-term survivors of HNC is encouragingly low. Trial registration: The study was registered in the German Registry for Clinical Studies (application No.: 00017122). Date of registration: 15.08.2019. https://drks.de/search/de/trial/DRKS00017122.
CRIS-Team Scopus Importer:2025-02-04
Keywords: head and neck cancer; MIDOS(2); patient-reported outcome; quality of life; symptom burden; UW QoL

Systematic classification of confocal laser endomicroscopy for the diagnosis of oral cavity carcinoma - Sievert, Matti; Oetter, Nicolai; Mantsopoulos, Konstantinos; Gostian, Antoniu-Oreste; Müller, Sarina Katrin; Koch, Michael; Balk, Matthias; Thimsen, Vivian; Stelzle, Florian; Eckstein, Markus; Iro, Heinrich; Goncalves, Miguel (Oral Oncology, 2022)
Introduction: Confocal laser endomicroscopy (CLE) is an optical imaging technique that allows in vivo microscope-like images of the upper aerodigestive tract's mucosa in 1000-fold magnification. The assessment of morphological tissue characteristics for the correct differentiation between healthy and malignoma suspected mucosa requires strict evaluation criteria. This study aims to validate a score for oral cavity squamous cell carcinoma (OCSCC) diagnostic. Methods: We performed CLE and examined a total of twelve patients. All 95 sequences (778 s, 6224 images) originate from the area of the primary tumor 260 s, 2080 images) and unsuspicious mucosa of the oral cavity (518 s, 4144 images). Specimen were taken at corresponding locations and analyzed histologically in H&E staining as a reference standard. A total of eight examiners (four experienced and four inexperienced) evaluated the sequences based on a scoring system. The primary endpoints are sensitivity, specificity, and accuracy. Secondary endpoints are inter-rater reliability and receiver operator characteristics. Results: Healthy mucosa showed epithelium with uniform size and shape with distinct cytoplasmic membranes and regular vessel architecture. CLE of malignant cells demonstrated a disorganized arrangement of variable cellular morphology. We calculated an accuracy, sensitivity, specificity, PPV, and NPV of 88.7 %, 90.1 %, 87.4 %, 87.5 %, and 90.0 %, respectively, with inter-rater reliability and κ-value of 0.775, and an area under the curve of 0.935. Conclusions: The results confirm that this scoring system is applicable in the oral cavity mucosa to classify benign and malignant tissue.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Carcinoma; Squamous cell/diagnosis; Confocal laser endomicroscopy; Early detection of cancer*; Endoscopy; Fluorescence; Fluorescent dyes; Head and neck cancer; Head and neck neoplasms/diagnosis; Head and neck neoplasms/pathology*; Humans; Lasers; Margins of excision; Microscopy; Confocal/methods*; Mouth neoplasms*/diagnosis; Optical biopsy; Oral cavity squamous cell carcinoma; Safe surgical margins

The COVID-19 pandemic and its consequences for the diagnosis and therapy of head and neck malignancies - Rupp, Robin; de Vasconcelos Craveiro, Antonio; Allner, Moritz; Grundtner, P.; Eckstein, Markus; Hecht, Markus; Iro, Heinrich; Gostian, Antoniu-Oreste; Balk, Matthias (European Review for Medical and Pharmacological Sciences, 2022)
OBJECTIVE: The COVID-19 pandemic and the measures accompanying it have been accused of having a negative influence on the frequency and methods of treatment of various diseases including head and neck cancer (HNSCC). To go further into this assumption, the diagnoses made, and treatments performed at one of Germany's largest head and neck cancer centres were evaluated.
CRIS-Team WoS Importer:2022-02-04

The Effects of a “New Generation” of Heat and Moisture Exchangers in Laryngectomized Patients with Previous Heat and Moisture Changer Experience - Almajali, Omar; Balk, Matthias; Rupp, Robin; Allner, Moritz; Sievert, Matti; Iro, Heinrich; Schützenberger, Anne; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2023)
Objectives: To evaluate the effects of a new generation of heat and moisture exchangers (NG-HMEs) on pulmonary rehabilitation, quality of life, patient satisfaction, and usage patterns. Methods: A prospective observational study on 23 laryngectomized patients with prior HME experience from June 1, 2021 to November 30, 2021. Patients were interviewed at inclusion, after 6 weeks and after 12 weeks after the introduction of NG-HMEs. Two validated questionnaires were used to report pulmonary complaints and quality of life: the Cough and Sputum Assessment Questionnaire (CASA-Q), the European Quality of Life 5 Dimensions Index Score (EQ-5D Index Score), and the European Quality of Life 5 Dimensions Visual Analog Scale (EQ-5D-VAS). Usage patterns and patient satisfaction were reported using study-specific questionnaires. Results: The patients had an average age of 65.7 ± 6.8 years, with 87% being male, on average 33.7 ± 35.3 months after total laryngectomy (TLE). NG-HMEs were used for a mean of 21.87 ± 4.63 hours/day (P =.034). After 12 weeks of use, patients reported the following changes in the CASA-Q domains: cough symptoms (+5; P =.663), cough impact (0; P =.958), sputum symptoms (+8; P =.13), and sputum impact (+3; P =.489). The EQ-5D index score increased (+0.024; P =.917) as well as the EQ-5D VAS (+0.8; P =.27). All patients rated their experience with NG-HMEs with ≥3 out of 5. The patients who used NG-HMEs as instructed (n = 13) reported more profound changes in the CASA-Q domains: cough symptom (+11; P =.129), cough impact (+7; P =.209), sputum symptom (+11; P =.123), and sputum impact (+10; P =.102). Conclusions: Our results show that NG-HMEs could have a positive clinical impact on pulmonary rehabilitation after TLE, even in HME-experienced patients. The use of NG-HMEs does not affect the quality of life. The possible effects of NG-HMEs require further evaluation in long-term studies to fully assess their efficacy.
CRIS-Team Scopus Importer:2023-10-20
Keywords: devices; pulmonary rehabilitation; quality of life; total laryngectomy

The modified Polsby–Popper score, a novel quantitative histomorphological biomarker and its potential to predict lymph node positivity and cancer-specific survival in oral tongue squamous cell carcinoma - Csűry, Tamás Dániel; Csűry, Anna Zsófia; Balk, Matthias; Kist, Andreas; Rupp, Robin; Müller, Sarina Katrin; Sievert, Matti; Iro, Heinrich; Eckstein, Markus; Gostian, Antoniu-Oreste (Cancer Medicine, 2023)
Background: The significance of different histological spreading patterns of tumor tissue in oral tongue squamous cell carcinoma (TSCC) is well known. Our aim was to construct a numeric parameter on a continuous scale, that is, the modified Polsby–Popper (MPP) score, to describe the aggressiveness of tumor growth and infiltration, with the potential to analyze hematoxylin and eosin-stained whole slide images (WSIs) in an automated manner. We investigated the application of the MPP score in predicting survival and cervical lymph node metastases as well as in determining patients at risk in the context of different surgical margin scenarios. Methods: We developed a semiautomated image analysis pipeline to detect areas belonging to the tumor tissue compartment. Perimeter and area measurements of all detected tissue regions were derived, and a specific mathematical formula was applied to reflect the perimeter/area ratio in a comparable, observer-independent manner across digitized WSIs. We demonstrated the plausibility of the MPP score by correlating it with well-established clinicopathologic parameters. We then performed survival analysis to assess the relevance of the MPP score, with an emphasis on different surgical margin scenarios. Machine learning models were developed to assess the relevance of the MPP score in predicting survival and occult cervical nodal metastases. Results: The MPP score was associated with unfavorable tumor growth and infiltration patterns, the presence of lymph node metastases, the extracapsular spread of tumor cells, and higher tumor thickness. Higher MPP scores were associated with worse overall survival (OS) and tongue carcinoma-specific survival (TCSS), both when assessing all pT-categories and pT1-pT2 categories only; moreover, higher MPP scores were associated with a significantly worse TCSS in cases where a cancer-free surgical margin of <5 mm could be achieved on the main surgical specimen. This discriminatory capacity remained constant when examining pT1-pT2 categories only. Importantly, the MPP score could successfully define cases at risk in terms of metastatic disease in pT1-pT2 cancer where tumor thickness failed to exhibit a significant predictive value. Machine learning (ML) models incorporating the MPP score could predict the 5-year TCSS efficiently. Furthermore, we demonstrated that machine learning models that predict occult cervical lymph node involvement can benefit from including the MPP score. Conclusions: We introduced an objective, quantifiable, and observer-independent parameter, the MPP score, representing the aggressiveness of tumor growth and infiltration in TSCC. We showed its prognostic relevance especially in pT1-pT2 category TSCC, and its possible use in ML models predicting TCSS and occult lymph node metastases.
CRIS-Team Scopus Importer:2023-12-29
Keywords: computer-assisted image analysis; squamous cell carcinoma of head and neck; survival analysis; tongue cancer

The Offprint of an Abnormal Pre-Parotidectomy Electrodiagnostic Finding in a Normally Functioning Facial Nerve: Correlation with Intraoperative Findings, Histology and Postoperative Facial Nerve Function† - Katheder, Verena; Sievert, Matti; Müller, Sarina Katrin; Thimsen, Vivian; Gostian, Antoniu-Oreste; Balk, Matthias; Rupp, Robin; Iro, Heinrich; Mantsopoulos, Konstantinos (Journal of Clinical Medicine, 2022)
The aim of this study was to search for associations between an electrodiagnostically abnormal but clinically normal facial nerve before parotidectomy and the intraoperative findings, as well as the postoperative facial nerve function. The records of all patients treated for parotid tumors between 2002 and 2021 with a preoperative House–Brackmann score of grade I but an abnormal electrophysiologic finding were studied retrospectively. A total of 285 patients were included in this study, and 222 patients had a benign lesion (77.9%), whereas 63 cases had a malignant tumor (22.1%). Electroneurographic facial nerve involvement was associated with nerve displacement in 185 cases (64.9%) and infiltration in 17 cases (6%). In 83 cases (29.1%), no tumor–nerve interface could be detected intraoperatively. An electroneurographic signal was absent despite supramaximal stimulation in 6/17 cases with nerve infiltration and in 17/268 cases without nerve infiltration (p < 0.001). The electrophysiologic involvement of a normal facial nerve is not pathognomonic for a malignancy (22%), but it presents a rather rare ( 6%) sign of a “true” nerve infiltration and could also appear in tumors without any contact with the facial nerve ( 29%). Of our cases, two thirds of those with an anatomic nerve preservation and facial palsy had already directly and postoperatively recovered to a major extent in the midterm.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Electromyography; Electroneurography; Facial nerve; Facial paralysis; Infiltration; Parotidectomy; Tumor

Time dependency of adjuvant therapy in advanced head-and-necksquamous-cell-carcinoma of unknown primary (CUP)-patients - Balk, Matthias; Rupp, Robin; Grundtner, Philipp; Müller, Sarina Katrin; Allner, Moritz; Traxdorf, Maximilian; Eckstein, Markus; Hecht, Markus; Iro, Heinrich; Gostian, Antoniu-Oreste (ORAL ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-07-16